Osztrák és nyugatnémet államelméleti irányzatok a II. világháború után - Maróti, Dávid (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2023)
In both the former West German and Austrian state theory, examination of the relationship to the former statehood has emerged. At the centre of Austrian academic discourses, tendencies were about continuity with the First Republic or the lack of it and were primarily centred around the Anschluss issue. Debates on state theory were essentially determined by analytical aspects of whether the Austrian state had ceased to exist as part of the Third Reich, with the result that a new state was created in 1945, or whether the Austrian state continued to exist under German authority, in which case we can only speak of its incapacity. Representatives of the West German tendencies of state theory examined the issue of legal continuity with the German Reich who analysed this issue in much greater detail than the Austrian ones did. Reasons for this are that the turning points of 1949 and 1954-55 were interpreted in different ways, and that Germany, unlike Austria, lost territories after World War II.